Evolution and long-term outcomes of combined immunodeficiency due to CARMIL2 deficiency - ÖZEN, AHMET OĞUZHAN; AYDINER, ELİF; BARIŞ, SAFA (WILEY, 2022)
Background Biallelic loss-of-function mutations in CARMIL2 cause combined immunodeficiency associated with dermatitis, inflammatory bowel disease (IBD), and EBV-related smooth muscle tumors. Clinical and immunological characterizations of the disease with long-term follow-up and treatment options have not been previously reported in large cohorts. We sought to determine the clinical and immunological features of CARMIL2 deficiency and long-term efficacy of treatment in controlling different disease manifestations. Methods The presenting phenotypes, long-term outcomes, and treatment responses were evaluated prospectively in 15 CARMIL2-deficient patients, including 13 novel cases. Lymphocyte subpopulations, protein expression, regulatory T (Treg), and circulating T follicular helper (cT(FH)) cells were analyzed. Three-dimensional (3D) migration assay was performed to determine T-cell shape. Results Mean age at disease onset was 38 +/- 23 months. Main clinical features were skin manifestations (n = 14, 93%), failure to thrive (n = 10, 67%), recurrent infections (n = 10, 67%), allergic symptoms (n = 8, 53%), chronic diarrhea (n = 4, 27%), and EBV-related leiomyoma (n = 2, 13%). Skin manifestations ranged from atopic and seborrheic dermatitis to psoriasiform rash. Patients had reduced proportions of memory CD4(+) T cells, Treg, and cT(FH) cells. Memory B and NK cells were also decreased. CARMIL2-deficient T cells exhibited reduced T-cell proliferation and cytokine production following CD28 co-stimulation and normal morphology when migrating in a high-density 3D collagen gel matrix. IBD was the most severe clinical manifestation, leading to growth retardation, requiring multiple interventional treatments. All patients were alive with a median follow-up of 10.8 years (range: 3-17 years). Conclusion This cohort provides clinical and immunological features and long-term follow-up of different manifestations of CARMIL2 deficiency.
Keywords: CARMIL2; CD28 co-signaling; combined immune deficiency; inflammatory bowel disease; long-term follow-up; T-CELLS; MUTATIONS; RLTPR; COSTIMULATION; AUTOIMMUNITY; DERMATITIS; DOCK8; CD28